Meeting minutes: WLE Management Committee. June 2019 - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Meeting minutes documenting key points and decisions from the CGIAR Research Program on Water, Land and Ecoystems (WLE) Management Committee meeting in London, UK, June 2019.